Tissue engineered pre-vascularized buccal mucosa equivalents utilizing a primary triculture of epithelial cells, endothelial cells and fibroblasts. (January 2016) - Heller, M.; Frerick-Ochs, E.V.; Bauer, H.-K.; Schiegnitz, E.; Flesch, D.; Brieger, J.; Stein, R.; Al-Nawas, B.; Brochhausen, C.; Thüroff, J.W.; Unger, R.E.; Brenner, W.
Abstract: Artificial generated buccal mucosa equivalents are a promising approach for the reconstruction of urethral defects. Limiting in this approach is a poor blood vessel supply after transplantation, resulting in increased morbidity and necrosis. We generated a pre-vascularized buccal mucosa equivalent in a tri-culture of primary buccal epithelial cells, fibroblasts and microvascular endothelial cells, using a native collagen membrane as a scaffold. A successful pre-vascularization and dense formation of capillary-like structures at superficial areas was demonstrated. The lumen size of pre-formed blood vessels corresponded to the capillary size in vivo (10–30 μm). Comparing native with a highly cross-linked collagen membrane we found a distinct higher formation of capillary-like structures on the native membrane, apparently caused by higher secretion of angiogenic factors such as PDGF, IL-8 and angiopoietin by the cells. These capillary-like structures became functional blood vessels through anastomosis with the host vasculature after implantation in nude mice. This in vitro method should result in an accelerated blood supply to the biomaterial with cells after transplantation and increase the succes rates of the implant material.